Low-grade sulfadoxine–pyrimethamine resistance in Plasmodium falciparum parasites from Lubango, Angola. (December 2016) - Kaingona-Daniel, Elsa; Gomes, Larissa; Gama, Bianca; Almeida-de-Oliveira, Natália; Fortes, Filomeno; Ménard, Didier; Daniel-Ribeiro, Cláudio; Ferreira-da-Cruz, Maria de Fátima
Abstract Background Malaria is a major parasitic disease, affecting millions of people in endemic areas.Plasmodium falciparum parasites are responsible for the most severe cases and its resistance to anti-malarial drugs is notorious. This is a possible obstacle to the effectiveness of intermittent preventive treatment (IPT) based on sulfadoxine–pyrimethamine (SP) cures administrated to pregnant women (IPTp) during their pregnancy. As this intervention is recommended in Angola since 2006, it has assessed, in this country, the molecular profiles inP. falciparum dhfr anddhps, two polymorphic genes associated to pyrimethamine and sulfadoxine resistance, respectively. Methods Blood samples from 52 falciparum patients were collected in Lubango, Angola andpfdhfr andpfdhps polymorphisms were analysed using nested-PCR and DNA sequencing. Results In thepfdhfr gene, the 108N mutation was almost fixed (98 %), followed by 59R (63 %), 51I (46 %), 50R and 164L (2 %, respectively). No 16V /S mutations were found. The most common double mutant genotype was CNRN (59 + 108; 46 %), followed by CI CN (51 + 108; 29 %) whereasIRN (51 + 59 + 108; 15 %), CNRN VL (59 + 108 + 164; 2 %) andRI CN (50 + 51 + 108; 2 %) triple mutant genotypes were detected. Investigations of thepfdhps gene showed that the 437G mutation was the most prevalent (97 %). Only two and one samples disclosed the 540E (7 %) and the 436A (3 %), respectively. Single mutant SG KAA (437; 86 %) was higher than SGE AA (437 + 540; 7 %) orAG KAA (436 + 437; 3 %) double mutants genotypes. No polymorphism was detected at codons 581G and 613T /S . Combiningpfdhfr andpfdhps alleles two triple mutant haplotypes (double mutant indhfr and single mutant indhps ) were observed: the ACI CN VI/SG KAA in 14 (56 %) samples and the ACNRN VI/SG KAA in five (20 %) samples. One quadruple mutant haplotype was detected (ACIRN VI/SG KAA) in six (24 %)P. falciparum samples. No quintuplepfdhfr –pfdhps mutant was noted. Conclusion pfdhfr andpfdhps gene mutations in isolates from Lubango are suggestive of a low-grade SP resistance and IPT for pregnant women and infant based on SP treatment could be effective. Routine molecular studies targeting polymorphism in these two genes need to be routinely conducted at country level.